SISTEM INFORMASI PENGELOLAAN BAHAN BAKU GUNA MENINGKATKAN EFEKTIVITAS LAPORAN PERSEDIAAN PRODUK PADA PT WIJAYA KARUNIA MEGAH - Antonius Ary Setyawan; Lucia Guntur Wijayanti; Agus Suparno (Electro Luceat, 2022)
Wijaya Karunia Megah Inc., Ltd. is a manufacturing company that provides fabrication services & building material applicators. Wijaya Karunia Megah Inc., Ltd. has not fully utilized information technology in its production process cannot check the availability of raw materials quickly, and takes a long time to generate product inventory reports. The purpose of this study is to develop an information system for managing raw material data at Wijaya Karunia Megah Inc., Ltd. to improve the efficiency of preparing product inventory reports. This research refers to the prototype development method, the programming language PHP framework Codeigniter, and MYSQL as the database. The results of this study are a material management information system website that can provide effective product inventory reports. The raw material processing system at Wijaya Karunia Megah Inc., Ltd. has gone through a systematic testing and evaluation process using paired sample t-test, black box testing, white box testing, and standard benefit testing of 25010. Testing using ISO 25010 gets an average result of functional suitability 94 .15%, performance efficiency 76.2%, usability 97.33%, reliability 92.2%, and maintainability 87.95%. We can conclude that the raw material processing information system helps PT Karunia Megah manage raw materials and provide product inventory reports effectively.